THE FUTURE OF ACCOUNTING. - Tiffany, Kenneth C. (The Accounting Review, 1961)
Abstract This article focuses on some of the problems facing the accounting society and suggests what the profession of accounting can do toward their future solutions. The problems are summarized as–To induce, rather than to force, business management and union labor to reach collective bargaining agreements, to save out of the flow of consumer purchasing power and corporate earnings, enough to equip with adequate tools and other capital assets, to achieve a more adequate understanding on the part of many more persons of the nature and workings of monetary system in its relationship to international and domestic commodity prices, wage rates, volume of business, volume of savings and levels of interest rates. To make progress towards something, that is a paradox and may turn out to be an impossibility. According to the author, accountants can and must play a leading role in disseminating the necessary information and knowledge and the extent to which Accountancy contributes to the necessary solution of these problems will determine the brilliance of its future.